The Role of Legal Institutions in Providing Information and Education About Restitution to Victims - Try Noldriyanto Rauf; Lisnawaty W. Badu; Avelia Rahmah Y. Mantali (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study analyzes the role of legal institutions such as the police, prosecutors, judges, and LPSK in providing information and education about restitution to victims of crime in Indonesia, with a focus on cases of sexual violence against children. Using a descriptive-analytical legal normative research method through a statute approach, conceptual approach, and case approach, this study examines key regulations such as Law No. 31 of 2014 in conjunction with Law No. 13 of 2006, PERMA No. 1 of 2022, PP No. 43 of 2017, and related jurisprudence. The results show that although legal institutions have an integral obligation from the investigation to the execution to convey restitution rights (material and immaterial), the implementation is still not proactive, there is a disconnect between institutions, and there is a lack of ongoing education, so that the effectiveness of restitution as restorative justice is not yet optimal. Recommendations include strengthening law enforcement agency training, mass socialization, and integrating procedures to ensure comprehensive victim recovery.